(untitled) (Costa Rican Journal of Guidance & Counseling, 2023)
The change from the face-to-face modality to a virtual mode, which occurred in universities as a result of the Covid-19 pandemic, has permeated multiple aspects of students’ lives, especially those who have entered higher education during this period. This study aims to analyze the social interaction of university students who began their studies during the pandemic. Six focus groups were conducted using a qualitative approach and a phenomenological method. In these groups participated thirty students from the first, second, and third years of the Counseling Major at the National University of Costa Rica. The findings show how student interaction has been possible through different technological resources. However, interpersonal relationships are less close and more stressful. Likewise, actions that favor the development of bonds, social skills, and prosocial behaviors are also observed. Finally, there is some difficulty in interacting during and after class sessions, which generates a greater sense of isolation. The results obtained allow the relevant entities to contextualize the environment that surrounds the learners to make decisions that make it possible to meet the needs of the student group to facilitate their integral development.